(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article deals with investigation of electromechanical and energetic characteristics of traction electric drive with vector systems of direct torque control. As a controlled object the traction asynchronous motor ДТА-1У1, which is used to drive the trolley-bus is considered. At the present time the usage of traction asynchronous electric drives for town transport is relevant. Due to development of power electronic devices and microprocessor-based control systems it became possible to replace DC electric drives with electric drives with asynchronous motors. The article contains brief description of two different types of control systems: field-oriented control (FOC) and direct torque control (DTC). Principles of work for both systems are considered and the main advantages and disadvantages associated with the use of these systems are pointed out. The models of both systems for traction asynchronous electric drive, built in modeling environment MATLAB/Simulink, are given in this article for further comparative analysis. As the main quality factor of control total harmonic distortion (THD) is used.